THE DEVELOPING OF COMMUNICATIVE LANGUAGE TEACHING ON THE SPEAKING SKILL OF STMIK ROYAL STUDENTS - Akmal, Akmal (Universitas Sari Mutiara Indonesia, 2019)
Communicative Language Teaching (CLT) is to advocate the teaching practices that develop learners’ abilities to communicate in a second language. It represents a change of focus on the language teaching from the learners’ need for developing communication skills. It aims to make the students more actively in English speaking at STMIK Royal Kisaran. Here, the lecturer give the motivation and suggestions to the students’ communication. It used the qualitative reserch design which the researcher used the description to answer the gaps of this research. The subjects are taken based on the randomese technique to get the results and they are only 25 students. the researcher gave some small hot topics, they can communicate and give good respons Most of the students are able to communicate in English even though it is a little or step by step. They can make small communication because the CLT makes communicate to their friends in English. Besides they can speak English, they are so comfortable in the CLT method in English Teaching.